Psychosocial Differences Between Female and Male Students in Learning Patterns and Mental Health-Related Indicators in STEM vs. Non-STEM Fields - María Natividad Elvira-Zorzo; Miguel Ángel Gandarillas; Mariacarla Martí-González (Social Sciences)
This study explores psychosocial differences in mental health indicators and learning patterns between male and female students to promote inclusion and equality in university classrooms, focusing on STEM and non-STEM fields. Using a holistic approach, five learning dimensions comprising a diversity-in-learning (DinL) construct were analyzed: Coping with Difficulties, Effort, Autonomy, Understanding/Career Interest, and Social Context. Psychosocial predictors, including paternal and maternal parenting patterns, were also examined. Data were collected through a questionnaire completed by 2443 students from 83 undergraduate and postgraduate programs. Results indicated that male students reported higher levels of autonomy, while female students reported experiencing more mental health difficulties related to learning. Gender differences in learning dimensions were more pronounced in non-STEM fields. Parental influences also differed, with fathers and mothers shaping male and female students’ learning patterns in ways that reflect traditional gender roles. The findings highlight the lasting effects of gender roles on learning habits and psychological challenges in higher education. The study underscores the importance of addressing gender patterns in parenting and education to support more women in pursuing STEM fields, ultimately fostering greater equality and inclusion in academia.